The potential of genetic engineering of plants for the remediation of soils contaminated with heavy metals. (5th July 2017) - Fasani, Elisa; Manara, Anna; Martini, Flavio; Furini, Antonella; DalCorso, Giovanni
Abstract: The genetic engineering of plants to facilitate the reclamation of soils and waters contaminated with inorganic pollutants is a relatively new and evolving field, benefiting from the heterologous expression of genes that increase the capacity of plants to mobilize, stabilize and/or accumulate metals. The efficiency of phytoremediation relies on the mechanisms underlying metal accumulation and tolerance, such as metal uptake, translocation and detoxification. The transfer of genes involved in any of these processes into fast‐growing, high‐biomass crops may improve their reclamation potential. The successful phytoextraction of metals/metalloids and their accumulation in aerial organs have been achieved by expressing metal ligands or transporters, enzymes involved in sulfur metabolism, enzymes that alter the chemical form or redox state of metals/metalloids and even the components of primary metabolism. This review article considers the potential of genetic engineering as a strategy to improve the phytoremediation capacity of plants in the context of heavy metals and metalloids, using recent case studies to demonstrate the practical application of this approach in the field. Abstract : Relying on plants to remove contaminants from polluted soils and waters, phytoremediation of inorganic pollutants is a relatively new and still evolving scientific discipline. To improve the efficiency of phytoremediation, researchers have produced transgenic high biomass plants by introducing genes involved in metal tolerance and accumulation, such as transporters, ligands or enzymes responsible for metal detoxification. This review summarizes recent progresses in this field, critically analysing the advantages and limitations, as well as proposing case studies to demonstrate the practical application of this approach in the field.